Crystal structures of apo and inhibitor‐bound TGFβR2 kinase domain: insights into TGFβR isoform selectivity. Issue 5 (1st May 2016) - Tebben, Andrew J.; Ruzanov, Maxim; Gao, Mian; Xie, Dianlin; Kiefer, Susan E.; Yan, Chunhong; Newitt, John A.; Zhang, Liping; Kim, Kyoung; Lu, Hao; Kopcho, Lisa M.; Sheriff, Steven
Abstract : To find a crystallization‐competent TGFβR2 kinase domain, several surface patches of potentially high‐entropy residues were identified. Constructs with these residues mutated to alanine were expressed and purified. One yielded crystals that routinely diffracted to better than 2 Å resolution. Comparison of structures of TGFβR1 and TGFβR2 with inhibitors explain the isoform selectivity. Abstract : The cytokine TGF‐β modulates a number of cellular activities and plays a critical role in development, hemostasis and physiology, as well as in diseases including cancer and fibrosis. TGF‐β signals through two transmembrane serine/threonine kinase receptors: TGFβR1 and TGFβR2. Multiple structures of the TGFβR1 kinase domain are known, but the structure of TGFβR2 remains unreported. Wild‐type TGFβR2 kinase domain was refractory to crystallization, leading to the design of two mutated constructs: firstly, a TGFβR1 chimeric protein with seven ATP‐site residues mutated to their counterparts in TGFβR2, and secondly, a reduction of surface entropy through mutation of six charged residues on the surface of the TGFβR2 kinase domain to alanines. These yielded apo and inhibitor‐bound crystals that diffracted to high resolution (<2 Å). Comparison of these structures with those of TGFβR1 reveal shared ligand contacts as well as differences in the ATP‐binding sites, suggesting strategies for the design of pan and selective TGFβR inhibitors.